2022
DOI: 10.1027/2151-2604/a000481
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the Explicit Power Motives

Abstract: Abstract. Power is an important motivator at work, particularly for leaders. However, power also relates to dark personality traits, which negatively affect employees and organizations. Therefore, we argue that a high explicit power motive is a double-edged sword depending on whether people desire power for dominance, prestige, or leadership. We explored these research questions in a cross-sectional ( N = 151 employees) and a prospective study ( N = 371 leaders). Both studies revealed that dominance is most st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…We proposed that cynics' preference for dominance-based strategies of power attainment backfires and renders them less (not more) likely to actually obtain power. We showed that-of all types of power motives-cynical individuals indeed seem to be guided by dominance (and not prestige or leadership), and prior studies linked dominance with various detrimental work behaviours that likely hinder individuals' career progression (Schattke & Marion-Jetten, 2021). However, it remains to be tested whether or not cynic's preference for dominance indeed undermines their power attainment.…”
Section: Gen Er a L Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We proposed that cynics' preference for dominance-based strategies of power attainment backfires and renders them less (not more) likely to actually obtain power. We showed that-of all types of power motives-cynical individuals indeed seem to be guided by dominance (and not prestige or leadership), and prior studies linked dominance with various detrimental work behaviours that likely hinder individuals' career progression (Schattke & Marion-Jetten, 2021). However, it remains to be tested whether or not cynic's preference for dominance indeed undermines their power attainment.…”
Section: Gen Er a L Discussionmentioning
confidence: 64%
“…Dominance is linked to mostly destructive behaviours and practices that will likely undermine (rather than contribute to) power attainment. Dominance is associated with counterproductive work behaviour (Schattke & Marion‐Jetten, 2021), use of threats and manipulative tactics (Case & Maner, 2014) and engaging in self‐interested actions at a cost of sacrificing the team's interests (Maner & Mead, 2010). In collaborative settings, dominance strategies are even met with resistance from group members (Ridgeway & Diekema, 1989) and yield harsher punishment in case of transgressions (Kakkar & Sivanathan, 2017).…”
Section: Power Attainmentmentioning
confidence: 99%
“…However, fearless dominance may actually capture the aspects of the psychopathic personality inventory that are not due to clinical psychopathy, which is captured by antisocial impulsivity (Miller & Lynam, 2012 ). Machiavellianism appears to have a particularly high association with the domineering facet, a smaller association with prestige, and no notable relationship with leadership (Schattke & Marion-Jetten, 2021 ; Semenyna & Honey, 2015 ).…”
Section: Where Did Dominance “Go” and Why?mentioning
confidence: 99%
“…Previous research has elaborated on why intrinsic motivation theory can influence employees’ propensity to engage in civic behavior. Intrinsic motivation refers to the internal factor of employee self-satisfaction ( Runge et al, 2020 ; Schattke and Marion-Jetten, 2022 ). Since OCBs are less likely to be formally rewarded than prescribed work behaviors, they are most likely to be driven by internal incentive channels ( Dermawan and Handayani, 2019 ; Ren et al, 2022 ).…”
Section: The Influencing Factors Of Ocb and Cwbmentioning
confidence: 99%